Devices Of Community, Architectures Of Visions: The Movie Theatre Of Quirino De Giorgio (Schermi. Storie e culture del cinema e dei media in Italia, 2024)
It is in the 1950s that the figure of Quirino De Giorgio (1907-1997), already a well-known architect of community spaces, comes to the fore in the feverish construction of movie theater that characterised the post-World War II peninsula. The essay investigates De Giorgio’s critical thinking by focusing on a case study devoted to the ‘microphysics’ of the movie theatres, understood as a series of devices, accessories, practices conceived to structure the spectator's cinematic experience (from the environ- mental disciplining of the audience to the construction of specific temporalities of programming), traces and spies of a material culture and a network of relationships.